PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN ISPRING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATERI PERPINDAHAN PANAS DI SEKOLAH DASAR - Ulfa, Agustina Miftachul; Supriyono; Mashfufah, Aynin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Science learning, especially heat transfer material in elementary schools, still applies conventional learning. This research aims to develop interactive multimedia assisted by iSpring as a learning medium to improve the cognitive learning outcomes of class V students on heat transfer material. The research sample consisted of fifth grade students at SDN 6 Ngunut selected using non-random sampling through a purposive sampling technique. This type of research is development (Research and Development) while the method used is the Borg and Gall model. The research was carried out at SDN 6 Ngunut involving 26 students. Data was collected through pre-test and post-test to measure improvements in learning outcomes. The results show that the validity of interactive multimedia as a result of the assessment by material experts is 78.75% in the valid category, the assessment by media experts is 75% in the valid category, and the assessment by educational practitioners is 95% in the very valid category. The effectiveness test results of this research show that interactive multimedia assisted by Ispring can significantly improve students' cognitive learning outcomes, as indicated by an increase in the average test score from pre-test to post-test. The average obtained from the pre-test was 59.84 and the post-test obtained an average score of 77.69. This shows an increase in value. This research is expected to contribute to implementing educational technology to improve the quality of learning in elementary schools